Analisis Kebijakan Pendanaan Jangka Panjang (Studi Kasus Pada Perusahaan Pt Sat Nusa Persada Tbk) - Nugraha, Adithya Aria; Purba, Jan Horas V; Sastra, Heri (LPPM Institut Bisnis dan Informatika Kesatuan, 2019)
Funding policy discusses sources of funds to be used in running a feasibly worthy investment. Management undertakes funding policy to obtain sources of funds to run company’s operating activities. This study’s goal is to identify sources of funding taken efficiently from internal sources such as shares capital, retained earnings, current year profit, or the source of the funds derived from external parties, in this case short-term and long-term debts. In this research, the author used ratios which are profitability, liquidity, activity, solvability and equity analysis. Based on the research, we can conclude that the company’s sales and liabilities are decreasing. The sales is unstable, and it is affecting the company in a way that it will possible not fit to apply for a larger loans. Thus, sales stability will affect on debt ratio.